2019
DOI: 10.1161/jaha.118.011440
|View full text |Cite
|
Sign up to set email alerts
|

Unreliable Estimation of Aortic Pulse Wave Velocity Provided by the Mobil‐O‐Graph Algorithm‐Based System in Marfan Syndrome

Abstract: Background Several devices have been proposed to assess arterial stiffness in clinical daily use over the past few years, by estimating aortic pulse wave velocity (PWV) from a single measurement of brachial oscillometric blood pressure, using patented algorithms. It is uncertain if these systems are able to provide additional elements, beyond the contribution carried by age and blood pressure levels, in the definition of early vascular damage expressed by the stiffening of the arterial wall. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…Previous studies have demonstrated that oscillometric PWV measurements (in-office and 24-h) underestimate cf-PWV, with differences more pronounced for the 24 h o-PWV (in-office mean difference 0.3 ± 1.1; 24-h mean difference 0.6 ± 1.3) [17]. In addition recent findings confirmed significantly lower 24-h o-PWV mean values compared with SphygmoCor inoffice [21].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Previous studies have demonstrated that oscillometric PWV measurements (in-office and 24-h) underestimate cf-PWV, with differences more pronounced for the 24 h o-PWV (in-office mean difference 0.3 ± 1.1; 24-h mean difference 0.6 ± 1.3) [17]. In addition recent findings confirmed significantly lower 24-h o-PWV mean values compared with SphygmoCor inoffice [21].…”
Section: Discussionmentioning
confidence: 79%
“…The reliability of o-PWVs provided by Mobil-O-Graph in specific subgroups of patients was recently questioned. In certain conditions exposing to early vascular aging, the oscillometric method was found to be inadequate in assessing arterial stiffness [ 21 ]. Moreover, a reduced agreement between PWV methods at higher levels of arterial stiffness was highlighted [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study has some limitations and several strengths. First, there is some debate about the reliability or not of the Mobile-O-Graph device for measuring AS in the general population and in patients with obesity or with Marfan’s syndrome [ 34 ]. Recently, a couple of studies have concluded that the oscillometric PWV of Mobil-O-Graph is explained almost entirely by age and SBP compared to carotid-femoral PWV [ 35 ] or to the invasive aortic PWV measurement [ 36 ], since their relationship is explained by shared associations with age and SBP.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence emphasizes the limitations of the algorithmic approach used by these ABPM devices in measuring central BP and PWV, because in some devices the algorithmic estimate of PWV is only based on squared age values and arm cuff systolic BP and is not really measured, thus being unable to pick‐up alterations in aortic wall properties in specific types of patients, for example, in Marfan's syndrome patients …”
Section: Devices and Softwarementioning
confidence: 99%